1982
DOI: 10.1128/jcm.16.1.96-98.1982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of direct and standard microtiter broth dilution susceptibility testing of blood culture isolates

Abstract: Turbid broth (0.5 ml) from blood culture bottles was inoculated into 0.5 ml of brain heart infusion broth, incubated for 3 to 6 h, diluted 1:500 in distilled water, and then inoculated directly into microtiter broth dilution susceptibility trays to test for minimal inhibitory concentrations. The results were compared to the standard tests performed 24 h later on colonies from subculture plates. The minimal inhibitory concentrations measured by these two methods were compared in 1,875 organism-antibiotic tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Kiehn et al (6) found only 0.7% categorical discrepancies between MicroScan MIC panels inoculated directly and by standard methodology from nonautomated blood culture systems. More recently, Pettigrew et al (13) compared results of direct inoculation from positive BacT/Alert bottles to Micro-Scan gram-positive and gram-negative rapid panels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiehn et al (6) found only 0.7% categorical discrepancies between MicroScan MIC panels inoculated directly and by standard methodology from nonautomated blood culture systems. More recently, Pettigrew et al (13) compared results of direct inoculation from positive BacT/Alert bottles to Micro-Scan gram-positive and gram-negative rapid panels.…”
Section: Discussionmentioning
confidence: 99%
“…Automated blood culture systems such as BacT/Alert and rapid MIC panels provided by automated bacterial identification and susceptibility testing systems such as MicroScan can potentially make direct susceptibility testing even more clinically valuable, allowing preliminary results in a matter of hours after growth is first detected in the blood culture bottle. Although the concept of direct inoculation of fluid from positive blood culture bottles into MIC panels was investigated in the early 1980s (6), no prospective evaluations by using the current MicroScan instrumentation, panels, software, and database, newer antimicrobials, or with more recently developed continuously monitoring blood culture instruments such as the BacT/Alert have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct antimicrobial susceptibility testing, either by agar disk diffusion (8,13,17) or broth dilution (14), of positive blood cultures containing bacteria was found to be feasible under most conditions. In addition, an impedimetric method has been developed for direct antimicrobial susceptibility testing of gram-negative bacilli (12) and for detection of oxacillin-resistant Staphylococcus aureus in blood cultures (36).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid techniques for testing the susceptibilities of organisms in blood cultures include the direct disk diffusion test (3,4,9,11,16) and automated or semiautomated instrument systems. Direct disk diffusion susceptibility testing of the organisms in positive blood cultures has been shown to be reliable for most microorganisms and antimicrobial agents (4,6,16,24); this technique can save 18 to 24 h compared to the times required for the standardized protocols.…”
mentioning
confidence: 99%